The Effects of COVID-19 Vaccination on Lactating Women: A Systematic Review of the Literature - Muyldermans, Joke; De Weerdt, Louise; De Brabandere, Larissa; Maertens, Kirsten; Tommelein, Eline (Frontiers in Immunology, 2022)
Objectives The availability of new vaccines against COVID-19 urges for guidance about vaccination during lactation. We aimed to review the literature to get an insight into the effects of COVID-19 vaccination on lactating women. Design Systematic review. Data Sources We searched Ovid Embase Classic+Embase, PubMed and BioMed Central for articles published between December 1st 2020 and December 31st 2021. Review Methods The search strategy contained terms and combinations related to COVID-19 vaccination during lactation, including the MeSH terms “COVID-19”, “COVID-19 Vaccines”, “SARS-CoV-2”, “Lactation”, “Breast Feeding”, “Pregnancy” and “Postpartum period”. The database search was completed with a manual search of the reference lists of included articles. Data concerning country, study period, number of participants, type of applied vaccine, time points of sampling and outcome measures were collected from the selected manuscripts. The data are summarized and synthesized in a descriptive way. Results 30 manuscripts were included in this review. Data on safety of COVID-19 vaccination during lactation indicate no severe vaccine-related local and systemic reactions, both after first and second dose, neither in the mother nor the nursing child. No significant amount of vaccine components seems to appear in breast milk. Milk supply data after vaccination are inconclusive as there are no quantitative data available. Some women however observe a temporary increase or reduction in milk supply, without long-term effects. All prospective cohort studies demonstrated the presence of SARS-CoV-2-specific antibodies in breast milk of nursing mothers vaccinated against SARS-CoV-2. Nearly all studies were conducted with mRNA vaccines. Conclusion There is evidence that the administration of a COVID-19 vaccine is safe and poses no additional risk to the breastfeeding woman or the breastfed baby. After vaccination of the mother during the lactation period, antibodies appear in the milk, which could protect the infant against COVID-19. Professional associations and government health authorities should therefore recommend offering COVID-19 vaccines to breastfeeding women, as the potential benefits of maternal vaccination while breastfeeding outweigh the risks.